2022
DOI: 10.15244/pjoes/152448
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Urban Ecological Environment Quality Based on Google Earth Engine: A Case Study in Xi’an, China

Abstract: The rapid expansion of cities has accelerated the impact of human activities on the ecological environment. Existing studies conducted quantitative evaluations of ecological environment quality through complex remote sensing image screening and processing. Dynamic monitoring and modeling based on cloud platform programming are still lacking at present. This paper evaluated the quality of the ecological environment in Xi'an in 2000Xi'an in , 2005Xi'an in , 2010Xi'an in , 2015Xi'an in , and 2020 using the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…The ecological environment quality in Xi'an will be seriously deteriorated by 2030 under the natural development scenario. However, Yang [9] dynamically monitored the ecological quality of Xi'an over the past 20 years and showed that the overall ecological quality of Xi'an will first decrease and then increase. The reason for this is that the theory that lucid waters and lush mountains are invaluable assets was proposed in 2005 and implemented nationwide in 2017, which has led to increased protection of the ecosystem.…”
Section: The Reasons and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ecological environment quality in Xi'an will be seriously deteriorated by 2030 under the natural development scenario. However, Yang [9] dynamically monitored the ecological quality of Xi'an over the past 20 years and showed that the overall ecological quality of Xi'an will first decrease and then increase. The reason for this is that the theory that lucid waters and lush mountains are invaluable assets was proposed in 2005 and implemented nationwide in 2017, which has led to increased protection of the ecosystem.…”
Section: The Reasons and Policy Implicationsmentioning
confidence: 99%
“…At present, studies on ecological environment quality assessment can be categorized into two types: calculating an RSEI based on remote sensing (RS) and calculating an ecological index (EI) based on a geographic information system (GIS) [7]. Among them, the RSEI is widely used due to the advantages of easy data acquisition, simple calculation methods, and objective and reliable assessment results [8][9][10], especially in the dynamic monitoring of ecological changes. Jing [11] used the RSEI to assess the ecological quality of the Ebi Lake wetland in Xinjiang and used the results to investigate the factors influencing the ecological quality, which provided an important basis for the ecological protection of the wetland.…”
Section: Introductionmentioning
confidence: 99%
“…Yang pointed out that there is a spatial spillover effect of urban environmental quality improvement. In order to avoid being in a disadvantageous position in urban competition, neighboring cities will learn from each other and follow each other's behavior [18]. As a new urban governance tool, the selection of civilized cities will undoubtedly stimulate the participation of local governments, which will emulate the excellent results already achieved by neighboring cities.…”
Section: Analysis Of the Spillover Effect Of City Honor On Enterprise...mentioning
confidence: 99%
“…Rural landscape ecology encompasses ecological, technical, and socio-cultural aspects, aiming to provide a suitable living environment and promote sustainable and diverse development. However, villages developed in desertification control areas pose a significant threat to the landscape pattern of rural human-land systems, as they are susceptible to external influences [13]. Hence, it is crucial to study how to enhance the rural landscape in cold and arid regions, considering ecological, social, and environmental factors.…”
Section: Introductionmentioning
confidence: 99%